Kitab Jawi Islamic thought of the Malay muslim scholars /c by Mohd. Nor bin Ngah - Mohd. Nor Ngah (Research notes and discussions paper, 1983)
The purpose of this book is to describe the contributions of Malay Muslim scholars to development of Islamic studies and to investigate the Islamic thought of Malay Muslim schlolars based on their works